(untitled) (Publicaciones en Ciencias y Tecnología, 2009)
In a Tikhonov regularization scheme to solve discrete linear ill-posed problems, selecting the parameter value is a key task. We use Wolfe inexact search on the L-curve to choose a λ regularization parameter value far from critical areas of the L-curve. Numerical results are shown comparing the inexact scheme with other exact searches.